2013
DOI: 10.1111/hsc.12074
|View full text |Cite
|
Sign up to set email alerts
|

Voices of care for adults with disabilities and/or mental health issues in Western Canada: what do families and agencies need from each other?

Abstract: Our purpose in this paper is to report on the frustrations and unmet needs of paid, formal caregivers and unpaid, family caregivers who together provide care to adults with disabilities and/or mental health issues. We conducted eight focus group interviews between November 2010 and June 2011 in two large, urban centres and one smaller centre in Western Canada. Four of our focus groups were with family members including adults with disabilities and/or mental health issues, their parents and their siblings, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…At the same time, a number of researchers point out difficulties associated with participation by people with disabilities [39,44,45] including needs for adapting processes through which informed consent, as well as study-topic related needs and preferences, are provided by participants. We refer readers to resources created to facilitate such adapted processes including Alberta Human Services, Adult Guardianship and Trusteeship Act (AGTA), which details guidelines for supporting adults who need assistance with decision making, and the Law Commission of Ontario, which provides a recent (2014) collection of commissioned papers pertaining to capacity, decision-making, and guardianship.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, a number of researchers point out difficulties associated with participation by people with disabilities [39,44,45] including needs for adapting processes through which informed consent, as well as study-topic related needs and preferences, are provided by participants. We refer readers to resources created to facilitate such adapted processes including Alberta Human Services, Adult Guardianship and Trusteeship Act (AGTA), which details guidelines for supporting adults who need assistance with decision making, and the Law Commission of Ontario, which provides a recent (2014) collection of commissioned papers pertaining to capacity, decision-making, and guardianship.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of staff approach is evidenced by Abbott & McConkey () who report that adults with developmental disabilities felt restricted in social inclusion opportunities when they perceived staff members to be treating them in childlike, or otherwise disrespectful, fashion. Correspondingly, Mooney & Lashewicz (), who conducted a series of focus groups with family members of adults with developmental disabilities and/or mental health disorders, presented family member reports of constraints to social inclusion that arise when staff members are self‐focused or otherwise preoccupied away from facilitating social inclusion opportunities. The same focus groups of family members described restrictions to self‐determination for their family member with a developmental disability and/or mental health disorder that occur when staff members misread and mishandle interactions, and consequently provoke behaviour outbursts.…”
Section: Introductionmentioning
confidence: 99%
“…Family members ordinarily wish to have continuing involvement in their relatives' lives after they have left their family home, as issues relating to their care remain deeply concerning to them (Bright et al, 2018). However, previous research has found that the collaboration between families and professionals may not always be straightforward (Bright et al, 2018;Mooney & Lashewicz, 2014;Redmond & Richardson, 2003;Ryan & Quinlan, 2018). Neither families nor professionals find it easy to develop collaborative relationships (Mooney & Lashewicz, 2014).…”
mentioning
confidence: 99%
“…However, previous research has found that the collaboration between families and professionals may not always be straightforward (Bright et al, 2018;Mooney & Lashewicz, 2014;Redmond & Richardson, 2003;Ryan & Quinlan, 2018). Neither families nor professionals find it easy to develop collaborative relationships (Mooney & Lashewicz, 2014). The main barriers for families are poor communication, inadequate support and coordination, a lack of information and lack of child or family centeredness (e.g., a concern with individual needs instead of what a service offers; Redmond & Richardson, 2003;Ryan & Quinlan, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation